A MODEL KONSEPTUAL E-COMMERCE TOKO BANGUNAN MENGGUNAKAN PENDEKATAN ENTERPRISE ARCHITECTURE SCORE CARD (EA SCORE CARD) - Handayani, Sri; Khanza, Muthia; Putra, Eko Manggara (Jurnal Media Infotama, 2021)
This E-Commerce System Changes Consumer Behavior From Online Shopping, So The Availability Of Well-Formatted Data, In One Well-Managed Data Source, Is Also A Goal Of Organizational Development. To Realize This, It Is Necessary To Choose An Accurate Strategy And Plan In Developing Enterprise Architecture (EA). You Need To Adopt Or Develop Your Own EA Framework For Enterprise Architecture. Enterprise Architecture Needs To Adapt And Follow Developments In Information And Technology That Are Currently Developing, As A Support For The Smooth Running Of Business. , Logical Organization Of Key Business Processes And Information Technology (IT) Capabilities That Reflect The Need For Integration And Standardization Of Operating Models. Enterprise Architecture Or Enterprise Architecture Is A Description Of The Stakeholder's Mission, In This Case The Leadership Of The Organization, Which Includes Information, Functionality/Usability, Organizational Location And Performance Parameters. Enterprise Architecture. Research Using EA Score Card Calculations For Users Obtained The Following Results: The Director Section With A Percentage Of 54%, The Warehouse Section 1-3 Ranging From 73-76% And The Outlet Section 1-3 With An Average Of 75-84%, Because If The Results If The Overall Architectural Maturity Test Is Achieved > 50% Then The Architecture Is Declared "Feasible", Getting Efficient Features, This Goal Is Achieved By Getting Features That Are Suitable For The Users Involved, Namely, Director, Warehouse And Outlet.